2012
DOI: 10.1016/j.jcat.2012.03.009
|View full text |Cite
|
Sign up to set email alerts
|

In situ XPS study of methanol reforming on PdGa near-surface intermetallic phases

Abstract: Graphical abstractHighlights► A Pd1Ga1 surface without Ga2O3 contact is inactive for CO2 formation in methanol steam reforming. ► In situ XPS spectroscopy showed that water activation is blocked on Pd1Ga1. ► The valence band electronic structure of Pd1Ga1 favors selective dehydrogenation to H2CO. ► In oxidative steam reforming, the Pd1Ga1 surface behaves like extended Pd. ► Thus, total methanol oxidation by O2 at low temperatures is predominant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
50
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 51 publications
(69 citation statements)
references
References 25 publications
7
50
3
Order By: Relevance
“…[60,61] Subsequent catalytic experiments on the MSR reaction revealed that multilayered PdGa NSIP was a poor, unselective catalyst, owing to its inability to activate water, as evidenced by the parallel, unselective production of mainly CO, some HCHO, and a small amount of CO 2 ( Figure 6). This result is in contrast to our MSR results on both supported and thinfilm PdGa/b-Ga 2 O 3 and Pd 2 Ga/b-Ga 2 O 3 [67,68] , as well as on the related PdZn NSIP, [60,61] which all showed a temperature range for increased CO 2 selectivity above about 530 K. [66] However, Figure 6, bottom, shows that the PdGa NSIP is capable of efficient oxygen activation, because, under oxidative steam-reforming conditions, a large amount of CO 2 is observed at low temperatures (491 K).…”
Section: Insights Into the Pdàga Systemcontrasting
confidence: 99%
See 1 more Smart Citation
“…[60,61] Subsequent catalytic experiments on the MSR reaction revealed that multilayered PdGa NSIP was a poor, unselective catalyst, owing to its inability to activate water, as evidenced by the parallel, unselective production of mainly CO, some HCHO, and a small amount of CO 2 ( Figure 6). This result is in contrast to our MSR results on both supported and thinfilm PdGa/b-Ga 2 O 3 and Pd 2 Ga/b-Ga 2 O 3 [67,68] , as well as on the related PdZn NSIP, [60,61] which all showed a temperature range for increased CO 2 selectivity above about 530 K. [66] However, Figure 6, bottom, shows that the PdGa NSIP is capable of efficient oxygen activation, because, under oxidative steam-reforming conditions, a large amount of CO 2 is observed at low temperatures (491 K).…”
Section: Insights Into the Pdàga Systemcontrasting
confidence: 99%
“…The water-activating role of the bimetalÀoxide contact became even more clear in our investigation of PdGa near-surface intermetallic phases ( Figure 5). [66] In situ XPS spectroscopy during the MSR reaction revealed no signs of (hydr)oxide species, Figure 2. Temperature-programmed MSR on a multilayer PdZn (1:1) alloy on Pd foil (top) versus the MSR on a "Zn-lean" monolayer PdZn surface and the MSR on clean Pd foil (bottom).…”
Section: Insights Into the Pdàga Systemmentioning
confidence: 99%
“…11 However, these early results were taken only in a limited coverage/temperature range (∼1.5 ML, 500 K) where buckling is close to zero.…”
Section: Ga/pd(111)mentioning
confidence: 99%
“…To correlate with the structure-insensitive total oxidation of methanol with O 2 toward CO 2 and water at low temperatures on the PdGa NSIP [2], two types of reforming reactions were studied in situ, namely “water-only” methanol steam reforming (MSR), corresponding to the “ideal” reaction CH 3 OH + H 2 O → CO 2  + 3H 2 , and oxidative steam reforming (OSR), whereby a certain added amount of O 2 may give rise to H 2 -formation stoichiometries ranging from partial methanol oxidation (CH 3 OH + 1/2 O 2  → CO 2  + 2H 2 ) to total oxidation (CH 3 OH + 3/2 O 2  → CO 2  + 2H 2 O). The interest in comparing MSR and OSR is basically derived from the fact that admission of a defined oxygen partial pressure to a methanol–water mixture is common to additionally suppress CO formation in the product stream by further CO oxidation and to compensate for the endothermicity of the pure methanol steam reforming reaction.…”
Section: Introductionmentioning
confidence: 99%